ANALISIS PENDEKATAN EKSPRESIF DALAM PUISI “TAK SEPADAN” KARYA CHAIRIL ANWAR - Lentauly Aritonang (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The expressive approach views literary works as direct reflections of the author’s inner experiences, emotions, and personality. This article aims to analyze the poem “Tak Sepadan” by Chairil Anwar using an expressive approach in order to reveal the relationship between the poet’s life experiences and the meaning of the poem. This study employs a descriptive qualitative method with content analysis techniques. The research data consist of the text of the poem “Tak Sepadan”, which is analyzed through intensive and repeated readings to identify expressive elements such as diction, metaphor, imagery, and symbols that represent the emotions of the lyrical “I.” The results of the analysis indicate that the poem “Tak Sepadan” reflects an experience of unrequited love as well as the poet’s awareness of the unequal position between himself and the beloved figure. The dominant emotions expressed include sadness, despair, alienation, and resignation, which are conveyed through metaphors of blind walls, fire, and self-destruction. These elements demonstrate a close connection between Chairil Anwar’s psychological condition and the poetic expression presented in the poem. Therefore, the expressive approach is proven to be relevant and effective in uncovering the meaning of the poem as an authentic representation of the poet’s inner struggle within the context of modern Indonesian literature. ABSTRAK Pendekatan ekspresif memandang karya sastra sebagai cerminan langsung dari pengalaman batin, emosi, dan kepribadian pengarang. Artikel ini bertujuan untuk menganalisis puisi “Tak Sepadan” karya Chairil Anwar dengan menggunakan pendekatan ekspresif guna mengungkap keterkaitan antara pengalaman hidup penyair dan makna puisi. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik analisis isi (content analysis). Data penelitian berupa teks puisi “Tak Sepadan” yang dianalisis melalui pembacaan intensif dan berulang untuk mengidentifikasi unsur-unsur ekspresif seperti diksi, metafora, citraan, dan simbol yang merepresentasikan emosi aku lirik. Hasil analisis menunjukkan bahwa puisi “Tak Sepadan” merefleksikan pengalaman cinta yang tidak berbalas serta kesadaran penyair akan ketidaksejajaran posisi antara dirinya dan sosok yang dicintai. Emosi dominan yang muncul meliputi kesedihan, keputusasaan, keterasingan, dan kepasrahan, yang diekspresikan melalui metafora dinding buta, api, dan kehancuran diri. Unsur-unsur tersebut menunjukkan adanya keterkaitan erat antara kondisi psikologis Chairil Anwar dengan ekspresi puitik yang dihadirkan dalam puisi. Dengan demikian, pendekatan ekspresif terbukti relevan dan efektif dalam mengungkap makna puisi sebagai representasi autentik pergulatan batin penyair dalam khazanah sastra Indonesia modern.